Competitive Performance Effects of Psychological Skill Training for Youth Swimmers. Issue 5 (October 2019) - Meggs, Jennifer; Chen, Mark A.
This study assessed the effect of two different psychological methods of skills training—self-talk and goal setting—on the swimming performance of youth swimmers. We allocated a convenience sample of club and county level youth swimmers ( N  = 49; M age  = 10.8, SD  = 1.25) to one of the three groups: self-talk, goal setting, or a control group engaged in no systematic psychological method of skills training. The groups were balanced in terms of competitive performance ability, age, and gender. Participants in the experimental conditions (self-talk and goal setting) completed a 5-week psychological skills intervention program and were measured on pre- and post-200-m swimming time in competition. After controlling for level of engagement in the program, analysis of covariance revealed a significant omnibus effect ( p  = .006, η p 2  = .20) with post hoc pairwise comparisons using magnitude-based statistics demonstrating that goal setting had a small positive effect compared with self-talk ( η 2  = .40; ± 0.45). Both self-talk ( η 2  = .50; ±0.48) and goal setting ( η 2  = .71; ±0.4) showed a small and moderate positive effect, respectively, relative to the control group. A social validation check confirmed that the swimmers found the intervention to be relevant, beneficial, and meaningful for improving performance. Psychological skills training may be effective in improving youth swimming performance; specific mechanisms underlying these benefits need further exploration.